Assessing access to care in a postpartum pelvic floor healing clinic - Singh-Varma, Anya; Wang, Li; Durst, Rachel; Moalli, Pamela A.; Giugale, Lauren E. (Frontiers in Urology, 2025)
IntroductionDisparities in pregnancy care exist in the United States, with limited data on access to specialized postpartum care for patients with complicated perineal lacerations. Our objective was to assess for disparities in access to a postpartum pelvic floor healing clinic following vaginal delivery. We hypothesized an underrepresentation of patients from more resource-deprived neighborhoods and those with longer travel times to the specialized clinic.MethodsThis is a retrospective cohort study comparing sociodemographic variables from a historical cohort of patients with third- and fourth-degree lacerations following vaginal delivery to a cohort of patients evaluated in a postpartum pelvic floor healing clinic. The primary outcome involved the comparison of the neighborhood area deprivation index between groups. The secondary outcomes included median household income, driving time, and distance to the hospital.ResultsPatients seen in the postpartum pelvic floor healing clinic were older (31.3 vs. 29.9 years, p < 0.01) and more likely to be multiparous (20.3% vs. 13.1%, p = 0.04). Race, ethnicity, and operative vaginal delivery were similar between groups. Patients from the postpartum pelvic floor healing clinic had more postpartum visits [3 (IQR 2–4) vs. 2 (IQR 1–2) visits, p < 0.01]. There was no significant difference in median neighborhood area deprivation indices [4 (IQR 2–7) vs. 5 (IQR 3–7), p = 0.06]. Fewer patients from the most resource-deprived neighborhoods were seen in the postpartum pelvic floor healing clinic, though this was not statistically significant (4.5% vs. 8.9%, p = 0.06). There were no significant differences in median household income or driving distance to the hospital between groups.ConclusionsAccess to a specialized postpartum pelvic floor healing clinic at our institution appears equitable across several sociodemographic factors.